Biogas Combustion Characteristics in a Concentric Flow Slot Burner: Effects of Co2 Concentration on Stability and Flame Structure - Kiriakos, Maged (AUC Knowledge Fountain, 2023)
Biogas combustion is affected by the concentration of carbon dioxide. The successful applications of Biogas as a sustainable renewable alternative fuel produced from waste depend on its combustion stability, heat release, and pollution level. The aim of the current study is to apply new combustion technology and study the stability and combustion characteristics of natural gas with different percentages of carbon dioxide from 0 to 40% simulating biogas fuel. The stability characteristics and the temperature profiles of turbulent planar flames at different levels mixture inhomogeneity are investigated and presented in this work. The flames are created in a newly developed concentric flow slot burner, CFSB, for different mixtures of 0, 10, 20, 30, and 40% of CO2 in natural gas. The stability characteristics, and the flame temperature measurements were carried out for different levels of mixture inhomogeneity and for the natural gas-CO2 mixtures. The main parameters of the current investigations are the mixture equivalence ratio, the Reynolds number, the level of mixture inhomogeneity, the air-to-fuel velocity ratio, and the air-to-fuel momentum ratio. The flames show highest stability at a partial premixing ratio equal to 5 for mixture inhomogeneity between fully premixed and non-premixed cases. At this level, the highest stability may be attributed to the generation of higher level of radicals from the rich pockets of the mixture. Lower stability was recorded at higher levels of CO2 concentration in the fuel, as expected due to the lower level of the fuel heating value and the temperature diluting effect of CO2. On the other hand, the stability is decreasing almost linearly by increasing the momentum ratio for all cases of CO2 concentration and all cases of mixture inhomogeneities. The temperature profiles show a reduction of the temperature level by increasing the CO2 concentration, as expected. The current work shows the advantage of using turbulent planar flames with an inhomogeneous mixture to stabilize biogas for practical combustion systems. So, biogas can successfully replace fossil fuels for a sustainable energy supply.